Membincang Pembelajaran Daring dari Sudut pandang Filsafat Teknologi dan Keterasingan Manusia - Nana Sutikna (Jurnal Ilmu Komunikasi Acta Diurna, 2021)
The Covid-19 pandemic, which has rapidly moved the offline mode of learning to online in the last two years, has brought many changes in the learning culture. To be able to continue to carry out learning activities, lecturers and students must inevitably become more closely related to technology. On the other hand, learning technology which was originally only a tool for lecturers during online learning actually takes on a role on the main stage and makes lecturers alienated in their own world. Through literature searches, this research seeks to uncover various forms of human relations with online learning technology while exploring the forms and causes of alienation experienced by the humans involved in it. Based on the findings of this study, it is known that humans build relationships with learning technology in four forms, namely embodiment relations, hermeneutics relations, alterity relations and background relations. Lecturers experience alienation in online learning because they are no longer able to make themselves fully embodied in their work; lecturers also lose their feudal authority which makes themselves no more than servants to learning machines as the main instrument. Therefore, a middle ground is needed that can still bridge the direct meeting of lecturers and students, which provides opportunities and space for students to not only transfer knowledge but also gain phenomenological and critical experiences in online learning that takes place, and hybrid learning methods are one of the alternatives.